2017
DOI: 10.1080/20002297.2017.1403843
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological parameters of naturally occurring periodontitis in the non-human primate Macaca mulatta

Abstract: Background: Non-human primates appear to represent the most faithful model of human disease, but to date the oral microbiome in macaques has not been fully characterized using next-generation sequencing. Objective: In the present study, we characterized the clinical and microbiological features of naturally occurring periodontitis in non-human primates (Macaca mulatta). Design: Clinical parameters of periodontitis including probing pocket depth (PD) and bleeding on probing (BOP) were measured in 40 adult macaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…The prevalence of Fn was assessed in 94% of patients, which was in accordance with the reported prevalence rates of 80%-100% [9,19,20]. Recent studies have shown that Fn is one of the furthermost abundant gram-negative anaerobes in mature supragingival and subgingival plaques of both healthy subjects and patients with periodontitis [21,22]. The less prevalent microorganism was Cg, affecting only 39 patients with chronic periodontal disease (16.5%).…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of Fn was assessed in 94% of patients, which was in accordance with the reported prevalence rates of 80%-100% [9,19,20]. Recent studies have shown that Fn is one of the furthermost abundant gram-negative anaerobes in mature supragingival and subgingival plaques of both healthy subjects and patients with periodontitis [21,22]. The less prevalent microorganism was Cg, affecting only 39 patients with chronic periodontal disease (16.5%).…”
Section: Discussionsupporting
confidence: 74%
“…However, we surprisingly found that the aveolar bone of MAM were in a healthy state without significant resorpsion. This result is contradicted by other studies suggesting obvious aveolar bone loss in middle-aged non-human primates [11,18,21], which should arose our high attention. Also, our results showed that the amount of alveolar bone resorbed in MAM was significantly less than MAH.…”
Section: Discussioncontrasting
confidence: 73%
“…type 2 diabetes, atherosclerosis, rheumatoid arthritis etc.) [9][10][11]. Thus, periodontal disease in the middle-aged population is attracting more attention and researchers are now trying to understand and tackle the disease of midl from multiple angles, especially the importance of oral microbiome.…”
mentioning
confidence: 99%
“…Thus, this study used the ligature-induced periodontitis nonhuman primate model, whose oral microbiome is more similar to that of humans (24,25), to provide new details on the kinetics of changes in the subgingival microbiome with the initiation, progression, and resolution of periodontal lesions. The investigation was also able to compare and contrast these changes across the life span and potentially identify unique characteristics of the microbiome in younger individuals who are less susceptible to periodontitis, as demonstrated in both humans and these nonhuman primates (26)(27)(28).…”
mentioning
confidence: 99%